Infeksi Oportunistik pada Orang dengan HIV/AIDS di RSUD Dr. Pirngadi Kota Medan Tahun 2018-2022 (SCRIPTA SCORE Scientific Medical Journal, 2024)
Background: The incidence of HIV/AIDS-related opportunistic infections should have decreased significantly in recent times due to antiretroviral therapy (ART). However, several factors such as patients diagnosed in the late stage of HIV infection, not starting and continuing ART, or ineffective ART will increase the incidence of opportunistic infections in PLWHA (people living with HIV/AIDS). Knowing about opportunistic infections in PLWHA can provide information about the types of opportunistic infections that occur most often and their epidemiology. Objectives: To identify opportunistic infections in PLWHA at RSUD Dr. Pirngadi Medan in 2018-2022. Methods: This study used analytical retrospective quantitative research using the Spearman correlation test by observing secondary data in the form of medical records with total sampling technique. Result: There were 253 PLWHA with opportunistic infections in 2018-2022 with the majority of male gender (82.6%), age group 25-32 years (37.5%), CD4 count